Seamless control for single‐phase high gain quasi‐switched impedance source multilevel inverter for distributed generation application - Ajaykumar Thummalagunta; Nita R. Patne; Kodandaram N (IET Power Electronics, 2021)
Abstract The single‐stage buck‐boost multilevel inverters are getting more attention even in low‐voltage and low power distributed generation applications due to high reliability with shoot‐through invulnerability. But the inherent boosting ability of most of the inventions is constrained by the device stresses and deprived performance at a low modulation index. In this study, a new hybrid quasi‐switched boost circuit is integrated with a reduced switch single‐phase multilevel inverter to accomplish a high gain single‐stage conversion at low device stress and high modulation index. It can be extended to a multi‐cell configuration for further enhancement of gain. Also, a control scheme is presented to achieve enhanced performance during standalone and grid‐connected modes. This scheme assists the need of providing reliable electrical supply to the critical local loads along with serving power to the main grid. It also provides islanding with a seamless transition for the period of grid failure. The proposed inverter's features, robustness, and flexibility of the control under both input voltage and output power disturbances make it more suitable for residential rooftop PV generation. A 500 W laboratory prototype is built for experimental verification. Both simulation and experimental studies validate the proposed theory.